Potential Unemployment Insurance Duration and Labor Supply: The Individual and Market-Level Response to a Benefit Cut - Andrew C. Johnston; Alexandre Mas (Institute of Labor Economics (IZA), 2020)
We examine how a 16-week cut in potential unemployment insurance (UI) duration in Missouri affected search behavior of UI recipients and the aggregate labor market. Using a regression discontinuity design (RDD), we estimate a marginal effect of maximum duration on UI and nonemployment spells of approximately 0.45 and 0.25 respectively. We use the RDD estimates to simulate the unemployment rate assuming no market-level externalities. The simulated response, which implies almost a one percentage point decline in the unemployment rate, closely approximates the estimated change in the unemployment rate following the benefit cut. This finding suggests that, even in a period of high unemployment, the labor market absorbed this influx of workers without crowding-out other jobseekers.
Keywords: J64; J65; D91; 330; employment; labor supply; benefits; unemployment insurance; unemployment